Kontribusi Marketing Syariah dan Citra Lembaga Dalam Mempengaruhi Keputusan Nasabah Menabung - Nur Anim Jauhariyah; Kiki Fitria; Mahmudah Mahmudah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
The purpose of this study 1) Knowing the influence of sharia marketing (X1) on customer decisions (Y) saving; 2) Determine the magnitude of the influence of the image of the institution (X2) on the customer's decision (Y) to save; 3) Knowing the simultaneous influence between sharia marketing (X1) and institutional image (X2) on Customer Decision (Y) saving. In this study using a quantitative approach to the type of survey research. Determination of the research sample using simple random sampling technique with 30 respondents. Research conclusions 1) Sharia marketing Bank Syariah Mandiri KC Genteng Banyuwangi Regency is one of the factors that influence customers' decision to save. The better the marketing of sharia is carried out, the more interested the public will be in saving at Syariah Syariah Bank KC Genteng Banyuwangi Regency; 2) the image of the institution of Bank Syariah Mandiri KC Genteng Banyuwangi Regency is one of the factors that influence the interests of customers to save. The better the image in the minds of the public, the more interested people will be saving at the Syariah Mandiri Bank KC Genteng Banyuwangi Regency; 3) sharia marketing (X1) and institutional image (X2) are the dominant variables on customer decisions (Y) saving at Bank Syariah Mandiri KC Genteng Banyuwangi Regency.